2009
DOI: 10.1111/j.1601-0825.2009.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the microbiology in patients with oral complaints and oral mucosal lesions

Abstract: This study showed a frequent presence of bacterial and fungal opportunists in patients with oral mucosal complaints, which were most common in immunocompromised individuals, however, also frequent in patients with local oral complaints only. Systematic evaluation of different treatment strategies is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 30 publications
(38 reference statements)
3
33
1
Order By: Relevance
“…In contrast, several studies have reported qualitative changes in oral flora during chemotherapy (23)(24)(25). Although such changes in oral flora are not well understood, the incidence of Candida species seems to increase after chemotherapy and radiotherapy for cancer (26), a trend also seen in oral flora obtained from immunocompromised hosts (27). In the present study, we found no significant differences in the prevalence of opportunistic microorganisms between the cancer treatment and control groups.…”
Section: Discussioncontrasting
confidence: 42%
“…In contrast, several studies have reported qualitative changes in oral flora during chemotherapy (23)(24)(25). Although such changes in oral flora are not well understood, the incidence of Candida species seems to increase after chemotherapy and radiotherapy for cancer (26), a trend also seen in oral flora obtained from immunocompromised hosts (27). In the present study, we found no significant differences in the prevalence of opportunistic microorganisms between the cancer treatment and control groups.…”
Section: Discussioncontrasting
confidence: 42%
“…Our findings support the idea that the composition of mucosal biofilms is inherently more complex than abiotic surface biofilms [18], [26] since host cells and the resident bacterial flora form part of the biofilm mass. The identification of bacteria within the biofilm mass in situ was not unexpected since bacteria are often co-isolated with Candida from ulcerative lesions of the oral mucosa in humans [27]. However for the first time we provide direct evidence for complex polymicrobial communities in pseudomembranous lesions using an experimental model of Candida infection.…”
Section: Discussionmentioning
confidence: 65%
“…The species distribution in oral mucosal or deep oral infections seems to be very similar to infections in other body sites, with the majority being classified as E. faecalis . Enteroccocci in oral mucosal infections are classical opportunists and, similar to other opportunists such as Candida spp., S. aureus and enteric rods (16), they appear commonly in patients who are immunosuppressed for various reasons. This was also the case in this study, where the patients were generally older and where 62.8% had general and systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on enterococci in oral mucosal lesions (15). Studies on compromised patients (16–18) have reported higher levels of enterococci than in healthy subjects. In the above-cited studies, enterococci are rarely specified and characterized with respect to phenotype, virulence and antibiotic susceptibility.…”
mentioning
confidence: 99%